Employee Perception of Employee Performance Assessment at The Ministry of Health Polytechnic Surabaya - Mahaputri, Citra; Yaimin, Yaimin (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study aims to identify employee perceptions of performance appraisals at the Surabaya Ministry of Health Polytechnic. Effective performance appraisals are important to improve employee motivation, well-being, and the quality of institutional services. Carried out from July to October 2024, this study involved all employees as participants and used a descriptive study method. The study population consisted of 90 employees, with data collected through an online questionnaire that measured various aspects of perception such as fairness, satisfaction, transparency, and objectivity. The results of the study showed that the majority of employees (42.2%) considered the performance appraisal process to be fair, while 38.9% considered it quite fair. Most respondents (48.9%) were satisfied with the existing assessment system, and 47.8% agreed that the assessment results were fair. However, 26.7% of employees feel that their work motivation is affected by the results of the assessment. In terms of transparency, 37.8% of employees feel that the assessment process is quite transparent, and 44.4% feel that the system is consistent and objective. Most employees (71.1%) have taken part in performance-related training, and 36.7% believe the results of the assessment can help them develop their careers. Although 41.1% of employees did not feel the negative impact of the assessment on well-being, this study concluded that employee perceptions tend to be positive. However, further efforts are needed to improve understanding and communication regarding the assessment process so that employees feel more engaged and motivated